Tricoumaroylspermidine from rose exhibits inhibitory activity against ethanol-induced apoptosis in HepG2 cells. Issue 13 (21st May 2021) - Zhou, Qian; Wang, Lanxiang; Liu, Bin; Xiao, Jianbo; Cheng, Ka-Wing; Chen, Feng; Wang, Mingfu
Abstract : Hepatocyte apoptosis is involved in the pathogenesis of alcohol-associated liver disease (ALD) and anti-apoptotic agents/extracts are thereby of great importance in the prevention/treatment of ALD. Abstract : Hepatocyte apoptosis is involved in the pathogenesis of alcohol-associated liver disease (ALD) and anti-apoptotic agents/extracts are thereby of great importance in the prevention/treatment of ALD. In this study, the protective effects of 10 edible flowers against ethanol-induced cell death were investigated in HepG2 cells, with rose ( Rosa rugosa ) showing the strongest activity. Therefore, rose was chosen for further separation and purification of bioactive fractions. A special fraction, SLs, was found to significantly increase the viability of EtOH-treated cells and attenuated EtOH-induced apoptosis partially via the activation of the AMPK/SIRT1 signaling pathway. Chromatographic analysis identified a series of hydroxycinnamic acid amides, kaempferol glycosides, and quercetin glycosides in this fraction, while the following intracellular uptake and cytotoxicity studies revealed that N 1, N 5, N 10-( E )-tri- p -coumaroylspermidine (a hydroxycinnamic acid amide) in this fraction exhibited remarkable hepatoprotective activity with similar effective dosage to sulforaphane. Hence, our results highlighted the anti-alcohol and hepatoprotective benefits of consuming rose.